Perancangan desain UI/UX website Artealogic sebagai media portofolio, produk, serta kampanye pentingnya branding dan bisnis bagi Generasi Z - Abiyaksa, Diaz (Universitas Ciputra Surabaya, 2024)
In designing the user interface (UI/UX) for the Artealogic website, the main focus is on the portfolio, campaigns, and introducing Generation Z businesses to the public. This research utilizes quantitative methods to delve into user needs and analyze the impact of development strategies, considering key elements such as page layout, color selection, typography, and intuitive navigation. The research highlights the urgency of optimal user experience as the focal point of UI/UX design. User needs analysis involves surveys aimed at identifying the expectations, habits, and preferences of Generation Z. Literature studies include a deep understanding of current design trends and effective UI/UX principles. Market research is conducted to analyze consumer behavior, detect color preferences, and evaluate visually appealing displays for the target audience. Design strategies involve selecting layouts that allow for clear information arrangement, using colors that reflect the brand and Generation Z identity, and implementing comfortable interface designs. Intuitive navigation design is considered to ensure users can easily navigate the provided content. The resulting website prototype reflects continuity among design elements to provide an engaging and consistent brand impression. The outcome of this design is expected to provide a strong foundation for Artealogic to compete in the digital realm. Through the development of a website that meets criteria and provides optimal experiences, Artealogic is expected to increase brand exposure, expand market share, and successfully enter competitive markets. By combining innovative design with an understanding of Generation Z audience needs.